Analysis of the low density lipoprotein receptor gene (LDLR) mutation spectrum in Russian familial hypercholesterolemia - V. B. Vasilyev; F. M. Zakharova; T. Yu. Bogoslovskaya; M. Yu. Mandelshtam (Вавиловский журнал генетики и селекции)
Familial hypercholesterolemia (FH) is a very common human hereditary disease in Russia and in the whole world with most of mutations localized in the gene coding for the low density lipoprotein receptor (LDLR). The object of this review is to systematize the knowledge about LDLR mutations in Russia. With this aim we analyzed all available literature on the subject and tabulated the data. More than 1/3 (80 out of 203, i. e. 39.4 %) of all mutations reported from Russia were not described in other populations. To date, most LDLR gene mutations have been characterized in large cities: Moscow (130 entries), Saint Petersburg (50 entries), Novosibirsk (34 mutations) and Petrozavodsk (19 mutations). Other regions are poorly studied. The majority of pathogenic mutations (142 out of 203 reported here or 70 %) were revealed in single pedigrees; 61 variants of mutations were described in two or more genealogies; only 5 mutations were found in 10 or more families. As everywhere, missense mutations prevail among all types of nucleotide substitutions in LDLR, but the highest national specificity is imparted by frameshift mutations: out of 27 variants reported, 19 (or 70 %) are specific for Russia. The most abundant in mutations are exons 4 and 9 of the gene due to their largest size and higher occurrence of mutations in them. Poland, the Czech Republic, Italy and the Netherlands share the highest number of mutations with the Russian population. Target sequencing significantly accelerates the characterization of mutation spectra in FH, but due to the absence of systematic investigations in the regions, one may suggest that most of LDLR mutations in the Russian population have not been described yet.